PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIIIC SMP TELEKOMUNIKASI PEKANBARU - Siti Aisyah; Sakur Sakur; Syofni Syofni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was motivated by the problems that occurred in the VIIIC class of SMP Telekomunikasi Pekanbaru and the result of learning mathematics which is still under the KKM with percentage 42,85% on subject that related to Pythagoras theorem. This research aims to improve the learning process and improve student learning achievement by applying cooperative learning model with structural Numbered Heads Together (NHT) approach. This type of research is a classroom action research with two cycles. The data was collected by doing observation of teachers and students activities and formative test. The data analysis of the research results showed that the weakness in cycle I has been improved with improvement plan that will be done in cycle II, it means that there has been improvement in the learning process. In addition, the number of students who achieved KKM on the basic score, formative test I (first cycle), formative test II (second cycle) were 42,85%, 53,57%, dan 71,43%, respectively. The percentage of achievement of this KKM also shows improvement from before action to after action so that it can be said that student learning achievement also increase. The results of this research indicate that cooperative learning model with structural Numbered Heads Together (NHT) approach can improve the learning process and improve the learning achievement of mathematics students VIIIC of SMP Telekomunikasi Pekanbaru second semester of the academic year 2016/2017.Key Words: Math Learning Achievement, Cooperative Learning Model With Structural Numbered Heads Together (NHT) Approach, Clasroom Action Research.